Bioremediation: An effective way of environmental sustainability - S.M. Rezaul Karim; Ismail Sahid (2016)
The quality of life depends greatly on the sustainability of quality environment. With the evergrowing awareness of the pollution causing from all aspects of manufacturing processes, use of petroleum, recalcitrant pesticides, and disposal of municipal and animal wastes etc., there is an increase in political pressure to mitigate the problem all over the world including Malaysia. The effects of environmental pollution and the methods of bioremediation of the contaminants have been studied from the available literature on the subject. Different aspects of environmental contamination with different organic compounds and toxic heavy metals and their general sources have been pointed out. Bioremediation as a means of environmental sustainability along with its mechanism, prospective pollution fighting organisms, and techniques and strategies has been explained. The bioremediation activity in Malaysia is still in infancy stage. The area of priority research with an emphasis on Malaysia have been identified as – detailed survey on the contaminated sites and their sources all over the country, development of bio-techniques for detection of environmental toxicity; search for new microorganism which can detoxify and destroy different contaminants easily; development of novel biocatalyst which can function under extreme conditions of acidity, salinity, temperature and pressure; creation of genetically engineered microorganisms which can degrade the difficult-to-control pollutants; development of low-cost and most effective in-situ and ex-situ bioremediation technologies, and the use of multiple processes i.e. use of plants and microorganism together, and other methods such as land farming, nutrient supplements etc. Multidisciplinary approach in cooperation and coordination with engineering, microbiology, ecology, geology and chemistry should be followed for successful bioremediation and thereby to sustain the environment of the globe.